Maya [videorecording (DVD)] - Verdin, Julia; Velasquez, Patricia; Feliciana, Isabella; Budinich, Billy; Owen, Rena, 1962-; Montgomery, Anthony (Freestyle Digital Media, 2024)
A fifteen-year-old Maya is being raised in a broken household. Her mom, Camila, is a struggling alcoholic with an abusive boyfriend, Diego. When Maya is followed on social media by a cute guy named Ray, she begins to chat with him about her chaotic life. Ray and Maya start meeting up, and he quickly becomes her confidant. When Diego's abuse escalates at home and Camila turns a blind eye, Ray encourages Maya to run away with him. After being initially spoiled, Maya slowly begins to realize Ray has another agenda. Maya starts being set up with Ray's clients, along with his other girl Kayla. As Ray continues to pimp her out, Maya finds herself trapped with no way out. Meanwhile, Camila falls into despair and ends up overdosing. She agrees to get sober to get Maya back. However, the trauma that Maya has been through does not make her return as easy as hoped. Ray is determined not to lose his money-making asset while Camila is intent on not losing her daughter ever again.